Aloe Vera: A Potential Herb for Periodontitis Management - Wal, Pranay; Samal, Himansu Bhusan; Khare, Riya; Arora, Kunal; Soni, Mohit; Rathode, Shruti; Wal, Ankita (Current Traditional Medicine, 2025)
BackgroundThe Aloe Vera plant has been used in India for several decades for the treatment of periodontal disease. The plant has been considered to have antimicrobial and anti-inflammatory properties, but it is still used for the treatment of periodontitis inflammation.ObjectiveThe study's goal was to assess the function of Aloe vera in the treatment of periodontitis. The article summarized numerous clinical studies, trials reports, patent reports, and safety data in addition to the mechanism of action to provide an overview of Aloe Vera’s usefulness in the treatment of periodontitis.MethodsThe information for their review articles was acquired by using Google Scholar and PubMed as search engines, as well as a number of publishers, including Springer Nature, Bentham Science, Taylor & Francis, and Elsevier. ClinicalTrials.gov.in was referred to study the clinical trials data, and Google Patents was used as a search engine for collecting patent reports.ResultsAloe Vera is useful for Periodontitis prevention and treatment due to its anti-inflammatory, antibacterial, and antioxidant features. Aloe Vera can be used as an alternative to treat periodontitis and its related physiological effects such as gingivitis and mucositis, and various pre-clinical and clinical studies have been summarized that have demonstrated that using Aloe Vera significantly improved the mentioned conditions.ConclusionAloe Vera is an herb that may be used to treat periodontitis and its associated negative effects. However, more preclinical and clinical research, might contribute to raising awareness and managing periodontitis.
Keywords: gingivitis